70.3k views
3 votes
I need help in this plz!!!!

I need help in this plz!!!!-example-1
User Frollo
by
4.5k points

2 Answers

1 vote

Explanation:

1) = {5(x+y)} - 2x

= 5x + 5y - 2x

= 3x + 5y

2)= {2(p×q)} + (p×q)

= (2p×2q)+ p×q

= 4pq + pq

= 5pq

3)= 6a + (8b + 2a)

= 8a + 8b

= 8(a+b)

4)= 3x² + ( x²+7x)

= 4x² + 7x

= x(4x+7)

User Khirad Zahra
by
4.2k points
5 votes

Answer:

Explanation:

72) 5*(x +y) - 2x

= 5x + 5y - 2x {Distributive property}

= (5x - 2x) + 5y {Combine like terms}

= 3x + 5y

73) 2*(pq) + pq

= 2pq + pq {Combine like terms}

= 3pq

74) 6a + (8b + 2a)

= 6a + 2a + 8b {Combine like terms}

= 8a + 8b

75) 3*x² + (x² + 7x)

= 3x² + x² + 7x {Combine like terms}

= 4x² + 7x

User Dave Lawrence
by
4.4k points